Comparative study on tannin content from the barks, wood and leaves of Talisai (Terminalia catappa) and bakauan (Rhizopora apiculata). - Framo, Ma. Magnolia L.
Tannin from the barks, wood and of Talisai (Terminalia catappa) and bakauan (Rhizopora apiculata) were extracted with water and alcohol-ether mixture at 80 degrees centigrade. Qualitative analysis and quantitative determination of tannin were conducted for each species. Qualitative tests gave results for the presence of tannin in both species. Tannin gave white, yellow brown and greenish or bluish black precipitates with gelatin, acetic acid - lead acetate and ferric chloride tests. Quantitatively, bakauan tree have more tannin content compared with talisai. Among the three portions of the plant studied, the bark of both trees consistently gave the highest amount of tannin followed by the and wood given the lowest tannin content. Talisai bark was found to have 3.99 g, 3.17g in the and 1.70 g in the wood. On the other hand, tannin content of bakauan bark is 4.92 g, 3.60 g in the and 1.99 g in the wood.